Comparison of industrial wastes as a binder in the agglomeration of coal fines - Romanus Chinonso Uwaoma; C.N. Henning; J.R. Bunt; N.T. Leokaoke; H.W.J.P. Neomagus (Results in Engineering, 2022)
There is limited work reported in the literature on the use of waste material as a coal binder, and no study has reported the use of industrial petroleum waste as a binder for fine discard bituminous coal. In this study, the binding properties of five industrial wastes were evaluated to determine their efficacy in the agglomeration of Highveld inertinite-rich coal fines; four waste products from the petrochemical industry and one waste recycled low-density polyethylene (LDPE) were used as binders. Therefore, the addition of waste binders was investigated to use the briquettes as carriers to reduce waste. The compressive strength, CS (MPa), impact resistance index, IRI (−), friability index, FR (%), abrasion resistance, AR (%), and water resistance index, WRI (%) of the briquettes were determined to evaluate the mechanical strength of the briquettes. The binderless briquettes had a maximum CS of 3.4 MPa, higher than the minimum CS of bituminous coal (2.1 MPa). The optimal concentration for each binder, based on mechanical strength (CS, IRI, FR), was determined as 15% Binder A (4.1 MPa; 68; 80%), 20% Binder B (2.3 MPa, 87, 71%), 20% Binder C (8.2 MPa, 1000, 100%), 5% Binder D (2.4 MPa, 21, 46%) and 5% Binder E (5.3 MPa, 97, 52%). Briquettes bound with 20% Binder B and 5–10% Binder E were water-resistant. The briquettes were matched with suitable industrial processes based on the obtained mechanical strength and physiochemical properties. The binderless and the Binder B and D bound briquettes may be suitable for PCC boilers because their strength is high enough to enable transportation and low enough not to inhibit pulverising. Binders B, C and E bound briquettes may be more suited for use in a fixed-bed-‍gasifier. None of the binders was recommended for use in blast furnaces due to the high ash yield, low volatile matter content and lack of swelling properties.